THE ROLE OF THE SINGLE PARENT IN RUNNING A FAMILY LIFE IN RT 03 KELURAHAN AUR GADING - Hariyanti, Yuyun (Jurnal Kopendik, 2022)
This study aims to determine the role of single parent mothers in carrying out family functions and to find out the problems faced by single parent mothers in the family. This research method used is a qualitative approach using case study research methods. In this study, the researchers involved 3 participants, namely SE, MA and SH codes. The technique used in the withdrawal of participants is using a snowball sampling technique. The results of this study indicate that being a single parent is not easy because it requires a process in taking care of the household. The recreational function is a function that has not been carried out optimally by a single parent. Based on the fact that being a single parent woman will encounter difficulties and the heavy duty of being a double parent, so being busy being a single parent results in the recreational function being not fully implemented.